Corrosive injury of the upper gastrointestinal tract and its outcome at 3 months: an observational study - Datta, Raj Kumar; Hossain, Mohammad Iqbal; Podder, Subrata; Alam, Mohammad Jane; Islam, Mohammad Shohidul; Golam Kibria, M.; Ahmed, Faruque (International Journal of Research in Medical Sciences, 2024)
Background: Ingestion of corrosive substances can cause severe gastrointestinal (GI) tract damage, leading to life-threatening complications. The severity depends on the substance type, quantity, and intent behind ingestion. Early endoscopic evaluation is crucial for assessing injury extent and guiding management. This study aimed to evaluate the type and severity of upper GI mucosal injuries through early endoscopy, identify subsequent GI complications following corrosive ingestion, and assess patient outcomes three months post-ingestion. Methods: This prospective observational study was conducted in the Department of Gastroenterology at Dhaka Medical College Hospital from January 2017 to December 2017. A total of 89 patients aged 18 years and above with a history of corrosive ingestion, presenting within 72 hours, were included. Data on the type of corrosive agent, quantity consumed, and ingestion intent were collected. All patients underwent upper GI endoscopy to assess mucosal injury severity. Results: The study included 89 patients, predominantly young females (79.8% in the 18-27 age group) with a male-to-female ratio of 1:2.5. Most were Muslim (96.8%) and married (65.2%). Acid ingestion was reported by 78.7% of patients, with 71.9% ingesting household cleaners like harpic. initial symptoms included dysphagia and abdominal pain (both 56.2%). At three months, 80.9% had no complications, while 10.2% developed esophageal strictures, 12.4% had gastric outlet obstructions, and 2.2% died. Severe endoscopic mucosal injury (Zargar’s grade 3) was a significant risk factor for complications. Conclusions: Early endoscopic assessment is essential for predicting and managing the immediate and long-term complications of corrosive ingestion, significantly impacting patient outcomes.